Attachment of Ultralow Amount of Engineered Plant Viral Nanoparticles to Mesenchymal Stem Cells Enhances Osteogenesis and Mineralization. Issue 21 (16th September 2020) - Lin, Ying‐Ying; Schuphan, Juliane; Dickmeis, Christina; Buhl, Eva Miriam; Commandeur, Ulrich; Fischer, Horst
Abstract: Hydrogel‐based materials are widely used to mimic the extracellular matrix in bone tissue engineering, although they often lack biofunctional cues. In the authors' previous work, Potato virus X (PVX), a flexible rod‐shaped biocompatible plant virus nanoparticle (VNP) with 1270 coat protein subunits, is genetically modified to present functional peptides for generating a bone substitute. Here, PVX is engineered to present mineralization‐ and osteogenesis‐associated peptides and laden in hydrogels at a concentration lower by two orders of magnitude. Its competence in mineralization is demonstrated both on 2D surfaces and in hydrogels and the superiority of enriched peptides on VNPs is verified and compared with free peptides and VNPs presenting fewer functional peptides. Alkaline phosphatase activity and Alizarin red staining of human mesenchymal stem cells increase 1.2–1.7 times when stimulate by VNPs. Engineered PVX adheres to cells, exhibiting a stimulation of biomimetic peptides in close proximity to the cells. The retention of VNPs in hydrogels is monitored and more than 80% of VNPs remain inside after several washing steps. The mechanical properties of VNP‐laden hydrogels are investigated, including viscosity, gelling temperature, and compressive tangent modulus. This study demonstrates that recombinant PVX nanoparticles are excellent candidates for hydrogel nanocomposites in bone tissue engineering. Abstract : Plant virus nanoparticles, engineered with functional peptides, are laden in mesenchymal stem cell‐embedded hydrogels at an ultralow concentration for generating a bone substitute. Their competence in stimulation of mineralization and osteogenesis, and the superiority of enriched functional peptides on its surface are verified, demonstrating an excellent candidate for hydrogel composites in bone tissue engineering.